Social familiarity and spatially variable environments independently determine reproductive fitness in a wild bird - Gokcekus, S; Firth, JA; Regan, C; Cole, EF; Sheldon, BC; Albery, GF (University of Chicago Press, 2023)
The social interactions that an individual experiences are a key component of its environment and can have important consequences for reproductive success. The dear enemy effect posits that having familiar neighbors at a territory boundary can reduce the need for territory defense and competition and potentially increase cooperation. Although fitness benefits of reproducing among familiar individuals are documented in many species, it remains unclear to what extent these relationships are driven by direct benefits of familiarity itself versus other socioecological covariates of familiarity. We use 58 years of great tit (Parus major) breeding data to disentangle the relationship between neighbor familiarity, partner familiarity, and reproductive success while simultaneously considering individual and spatiotemporal effects. We find that neighbor familiarity was positively associated with reproductive success for females but not males, while an individual's familiarity with their breeding partner was associated with fitness benefits for both sexes. There was strong spatial heterogeneity in all investigated fitness components, but our findings were robust and significant over and above these effects. Our analyses are consistent with direct effects of familiarity on individuals' fitness outcomes. These results suggest that social familiarity can yield direct fitness benefits, potentially driving the maintenance of long-term bonds and evolution of stable social systems.